PRODUCT DEVELOPMENT OF MULBERRY FLAKY CHINESE PASTRY - Singsom, Susitar; Phuchan, Pakawadee (Life Sciences and Environment Journal, 2024)
This development of Mulberry Flaky Chinese Pastry aims to develop Flaky Chinese Pastry to have more nutrition, select a standard recipe that is well accepted by customers, and study the physical properties and chemical components of Mulberry Flaky Chinese Pastry. From the study of customer acceptance of Mulberry Flaky Chinese Pastry with 100 general customers using 9 - Point Hedonic Scales to evaluate appearance, color, smell, taste, texture, and overall satisfaction, customers prefer coconut milk as stirring ingredient in Mulberry Flaky Chinese Pastry most (p≤0.05). The value of L* a* b* are 17.92, 9.98, and 2.27 respectively. The chemical composition analysis of Mulberry Flaky Chinese Pastry with coconut milk showed that 100 g of moisture was 20.23%, 1.25% of ash, 3.44% of protein, 6.58% of fat, 68.50% of carbohydrate, 4.21 g of fiber, 346.98 kcal, 52.14 mg of anthocyanins, 203.63 mg GAE/g of phenolic compounds, and 236.72 mg Trolox of antioxidant capacity. the microbiological quality of Mulberry Flaky Chinese Pastry product was in accordance with the Thai community product standard No.115/2555